THE INFLUENCE OF ENTREPRENEURIAL KNOWLEDGE, EDUCATION, AND SKILL ON SMALL MEDIUM ENTERPRISES PERFORMANCE IN MANADO - Manampiring, Cicilia T. Manampiring; Massie, James D.D.; Worang, Frederik G. (Universitas Sam Ratulangi, 2020)
In line with the Indonesian government's economic development program, where the starting point is directed towards improving prosperity and poverty alleviation through economic empowerment of the people, it is estimated that Indonesia will need an additional 20 million new business units outside the agricultural sector in the next 15 years to increase the carrying capacity of economic growth and job creation for the Indonesian population. The development of new entrepreneurs related to efforts to grow a conducive business environment, fostering community willingness to entrepreneurship, improving the ability of the community to entrepreneurship. This research aims to find out the significant influence of entrepreneurial knowledge, education, and skill on small-medium enterprises in Manado simultaneously. The type of this research is a quantitative method. The results show that entrepreneurial knowledge, education, skills as the independent variable simultaneously affect business performance as the dependent variable. Based on the analysis, since entrepreneurial education is strong predictors of business performance, the factor was recommended to be a push to make the growth of the business performance of SMEs real, and companies should maintain a sustainable system both internally and externally so that in the future they can always maintain their performance. Keywords: entrepreneurial knowledge, entrepreneurial education, entrepreneurial skill, small-medium enterprises performance.